ECOLOGY OF DIGITAL ATTENTION AND STUDENT SELF-REGULATION: A CONCEPTUAL ANALYSIS OF CHARACTER EDUCATION IN THE PLATFORM ERA - Putra Asga Elevri; Yadi Ruyadi; Encep Syarief Nurdin; Asep Dahliyana (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The development of digital platforms has helped to reshape the learning, communication, entertainment, and social relations environment of adolescent students. In this context, digital attention is more proportionate to be understood not only through screen duration or device use settings, but also through media usage habits, social-pedagogical relationships, norms of technology use, and platform design and incentives as part of the student's digital environment. This article aims to compile a conceptual analysis of the relationship between the ecology of digital attention, adolescent self-regulation, and character education in the platform era. Using a conceptual study based on directed narrative literature, this article proposes